Pemanfaatan Kapang Aspergillus niger sebagai Inokulan Fermentasi Kulit Kopi dengan Media Cair dan Pengaruhnya Terhadap Performans Ayam Broiler - Akmal, Akmal; Filawati, Filawati (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2008)
During  the  study,  it  was  used      100  broiler  aged  7  days  and  5  treatment  ration  which  contain different fermented coffee pulp. The design used  in this study  was the block randomized design (BRD) with  5  treatmens.    Parameter  measured    were  ration  consumption,  weight  growth,  and  ration conversion. The  result  of  this  study  showed that  the  use  of  fermented  coffee  pulp  in  the  ration was  significantly effective (P<0,05)  on  the  weight  growth,  ration  consumption  and  ration  conversion.    It could be concluded  that fermented coffee pulp can be used up to 10% in the ration of the broiler